Targeting the molecular web of Alzheimer’s disease: unveiling pathways for effective pharmacotherapy - Devika Jadhav; Nikita Saraswat; Neeraj Vyawahare; Devendra Shirode (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2024)
Abstract Introduction Alzheimer’s disease is a neurocognitive disorder that affects elderly people by slowly impaired cognition, dementia, and gets worse with age. It slowly impacts the quality of life. Clinically, it is distinguished by a transition from episodic memory to a gradual reduction in cognitive ability leading to cognitive dysfunction. Neurofibrillary tangles and amyloid plaques are unique structures that are thought to have a role in the pathogenesis of Alzheimer's disease. In this review, we focus our attention on the risk factors, pathophysiology, etiology, epidemiology, stages, diagnosis, treatment, mechanisms, pathways, ongoing clinical trials data and risks potentially associated with the development of Alzheimer's disease. Short summary This review aims to extrapolate the information about Alzheimer's disease. Preliminary research was done by selecting reviews on PubMed, Elsevier, and Google open-access publications using the keywords like “Alzheimer, dementia, neurodegenerative, memory, amyloid β, mechanism of action, pathways”. Conclusion Here we show the discussion and interpretation of several signaling pathways in the pathogenesis of Alzheimer's disease such as amyloid β plaque cleavage, Metal ion hypothesis, amyloid β degradation, initiation of amyloidogenic and non-amyloidogenic pathway, oxidative stress hypothesis, Metabolic syndrome, insulin resistance and tau phosphorylation associated apolipoprotein- cholesterol, neurofibrillary tangles accumulation, and insulin resistance which are significant for better understanding of the disease initiation and progression. On studying the ongoing clinical trials, it was found that current drugs being tested are crenezumab, gantenerumab and sodium oligonucleotide. Graphical Abstract